The Ideal Legal Order for an Occupied Nation: Polish Commentary on Mitchell Franklin - John J. Czyzak (Washington University Law Quarterly, 1951)
During his service in the Armed Forces of the United States, Professor Mitchell Franklin wrote his now famous essay dealing with the subject of the legal system of Occupied Germany. The work appears to have received the attention of the bar of Poland, and was paraphrased in an issue of a Polish legal periodical devoted entirely to the problem of re-establishing the rule of law in Germany. Because of the continuing crisis in world politics, it seems worthwhile to examine once more the pattern of practices indulged in by German National Socialism. In an interesting article in the Georgetown Law Journal' Professor Charles M. Kneier discussed the matter of judicial review of the motives of city councils. He suggests that in general such councils are in a position similar to that of superior legislative bodies, although, in many states their activities are reviewable for fraud and the scope of review is broader than in the case of higher legislatures. Only in a few instances is it held that such ordinances may be reviewed when improper motives of councilmen are charged as affecting their votes. He observes that while the legislation of superior legislative bodies cannot be invalidated for fraud and corruption, ordinances, on the other hand, are commonly set aside for that reason. Ordinances involving franchises and contracts, being administrative, are declared to be subject to different considerations, being of a temporary character as distinguished from the more permanent character of legislation.
Keywords: Military occupation